2020
DOI: 10.1016/j.sdentj.2020.01.010
|View full text |Cite
|
Sign up to set email alerts
|

The impact of salivary lactoperoxidase and histatin-5 on early childhood caries severity in relation to nutritional status

Abstract: Introduction Early childhood caries is a multifactorial disease. Saliva plays an important role in initiation and protection against caries, and its composition is greatly affected by nutritional status. This study was conducted to determine the impact of salivary lactoperoxidase and histatin-5 on the severity of ECC in relation to nutritional status. Materials and methods The sample consisted of 120 children aged 5 years, classified into eight groups: mild ECC in under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…It can be hypothesized that the increase in histamine may be due to the increase in histidine, and the increase in histidine my be caused by the enhanced hydrolysis of histatins, since histatins is a histidine-rich homologous polypeptide. Our results are consistent with the findings from a study of Munther et al, which revealed decreased histatin-4 concentrations in the saliva of caries-active children ( Munther, 2020 ). However, further studies are needed to confirm the aforementioned hypothesis, i.e.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…It can be hypothesized that the increase in histamine may be due to the increase in histidine, and the increase in histidine my be caused by the enhanced hydrolysis of histatins, since histatins is a histidine-rich homologous polypeptide. Our results are consistent with the findings from a study of Munther et al, which revealed decreased histatin-4 concentrations in the saliva of caries-active children ( Munther, 2020 ). However, further studies are needed to confirm the aforementioned hypothesis, i.e.…”
Section: Discussionsupporting
confidence: 93%
“…Salivary histatins are a family of histidine-rich cationic homologous polypeptides with similar amino acid sequences, which are considered to be important components of non-immune host defense system in the oral cavity. Studies have confirmed that the concentrations of slivary histatin-5 was associated with the severity of caries, histatin-5 concentrations in saliva of children without caries was significantly higher than that of children with caries, which decreased gradually with the increase in caries severity ( Munther, 2020 ). Therefore, it is believed that salivary histatin-5 can be applied in the prevention and treatment of caries, especially in children with caries [ Jurczak et al., 2015 ; Munther, 2020 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…To date, there is no consensus as to whether histatin levels in saliva correlate with infection levels in the oral cavity. Comparisons of children or adult patients with and without dental caries have found no variation in salivary histatin levels, , higher salivary histatin levels in patients with caries, , and lower salivary histatin levels in patients with caries. Similarly, there is no clear correlation between histatin levels and the prevalence of oral C. albicans in healthy people but high histatin levels do correlate with high prevalence of oral candidiasis in immunocompromised patients .…”
Section: Discussionmentioning
confidence: 99%
“…Natural antimicrobial peptides are potential biomarkers because deregulation of antimicrobial peptides can affect the caries risk (Jurczak et al, 2015;Munther, 2020) or are genetic susceptibility markers of caries (Slebioda et al, 2020;Wu et al, 2020). It is suggested that a positive correlation exists between the salivary hBD-2 level and caries progression (Jurczak et al, 2015).…”
Section: Natural Antimicrobial Peptidesmentioning
confidence: 99%